A Financial Simulation Modeling for Major University in the Middle East - Ahmed Atef Bakhsh (Faculty of Industrial Technology Universitas Islam Indonesia, 2019)
In the present economic environment, it is critical for organizations to precisely monitor and forecast financial issues for better decision-making. This study constructed a model for the college of Engineering's financial operation of a major University in the Middle East by looking at the numbers of its revenues and expenses. Moreover, object-oriented simulation (OOS) tools is used for the financial model that support the subject matter experts in how the model can be used to help them make decisions regarding topics such as: does it make sense to introduce a new major now or in the future, should the college try to enroll more students, or even should a specific course be offered at a specific semester. The simulation model help in financial terms only.